(untitled) (Journal of Philosophy, Culture and Political Science, 2025)
This study examines the pivotal role of Higher Education Institutions (HEIs) in strengthening educational cooperation between the Republic of Korea and two strategically important regions: ASEAN and Central Asia. Through comparative analysis of student exchanges, faculty collaboration, and institutional support, the research identifies significant imbalances and challenges in these educational relationships. This study shows that the student mobility outlook exhibits extreme directional asymmetry, with far more students from both regions studying in Korea than vice versa. Faculty collaboration remains limited and narrowly focused on economic and political topics rather than comprehensive academic partnerships. Institutional support varies considerably, with both regions receiving less attention than East Asian studies in Korean academia. The paper argues that addressing these challenges through targeted interventions at student, faculty, and institutional levels can transform these predominantly elite-driven relationships into more balanced partnerships with broader societal engagement. By adopting a multi-stakeholder approach that emphasizes agency rather than structural constraints, this research demonstrates how Higher Education Institutions (HEIs) can serve as crucial bridges for sustainable and resilient bilateral relations between Korea and these regions. Keywords: higher education institutions, education cooperation, ASEAN-ROK relations, Central Asia-ROK relations, student mobility, faculty collaboration, institutional support, comparative education, educational diplomacy, soft power.